Moments of Peru at war: Testimony of a life dedicated to portraying reality, despite its severe limitations - Jiménez, Ernesto (2024)
Talking about internal war in Peru is doubly difficult. Because of the issue of political violence that we had to live with and our role as journalists in tow, away from the passions and standard bearers of the famous objectivity whose meaning hammered us every time we took the camera to record what happened. Then came the self-censorship that took us away from the flags that the participants brought as pretexts for the violence unleashed or to unleash. We were interested in the roots of this violence, its origins and the “why” in each case. Thus, we began to see what others did not see: the significance of our documents for history, for its reconstruction. Reviewing my experience of those years (half a century of journalistic work) I have managed to synthesize some objective, transcendental and valid criteria to contribute to history. My search spanned 14 years of conflict. From 1978 (the beginnings of land grabs) until 1992, when they captured the insurgent leaders of the Shining Path. Of course, there are thousands of unpublished images left in the archives. But the demands of the present testimony force us to choose the best (or the worst) of those moments.